2023
DOI: 10.1161/strokeaha.122.042335
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Intravenous Tenecteplase Versus Alteplase for the Treatment of Acute Ischemic Stroke: A Systematic Review and Meta-Analysis

Abstract: BACKGROUND: Prior systematic reviews have compared the efficacy of intravenous tenecteplase and alteplase in acute ischemic stroke, assigning their relative complications as a secondary objective. The objective of the present study is to determine whether the risk of treatment complications differs between patients treated with either agent. METHODS: We performed a systematic review including interventional studies and prospective and retrospective, obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Evidence from previous meta-analyses in AIS patients consistently suggests that the efficacy and safety of TNK is not inferior to ALT [ 22 , 34 36 ]. However, given the substantial impact of MT on AIS outcome [ 2 ], many studies have intentionally excluded patients undergoing MT from their study cohorts [ 22 , 34 36 ]. As a result, patients receiving MT were underrepresented in meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from previous meta-analyses in AIS patients consistently suggests that the efficacy and safety of TNK is not inferior to ALT [ 22 , 34 36 ]. However, given the substantial impact of MT on AIS outcome [ 2 ], many studies have intentionally excluded patients undergoing MT from their study cohorts [ 22 , 34 36 ]. As a result, patients receiving MT were underrepresented in meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In these 3 studies, 750 patients received A systematic review of 26 studies, including interventional, prospective, retrospective, and observational studies, evaluated complications following intravenous tenecteplase for ischemic stroke. 10 Fifteen of the 26 studies reported rates of angioedema, and among these patients, angioedema occurred in 0.56% of patients, with individual studies reporting rates of 0% to 2.8%.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of intravenous thrombolysis with tenecteplase in patients with AIS remains controversial. There are some evaluations of tenecteplase and alteplase in the treatment of AIS, e.g., a systematic review and meta-analysis by Rehman et al [ 15 ], which mainly explores different doses, and Rose et al [ 16 ], which focuses on the risk of complications associated with treatment with the two drugs. In addition, there are some network meta-analyses [ 17 , 18 ], but these include not only RCTs but also some other types of clinical studies, which will increase the publication bias of the article and thus have a certain impact on the accuracy of the results.…”
Section: Introductionmentioning
confidence: 99%